2017
DOI: 10.4187/respcare.05440
|View full text |Cite
|
Sign up to set email alerts
|

Smoke, Biomass Exposure, and COPD Risk in the Primary Care Setting: The PUMA Study

Abstract: Subjects with COPD from primary care had a higher exposure to biomass and smoking compared with non-COPD subjects. Smoking and biomass are both risk factors for COPD, but they do not appear to have an additive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…[33][34][35] Other evidence has illustrated via the possible roles regarding aging hallmarks including genomic instability, deregulated nutrient sensing, cellular senescence and stem cell exhaustion that disturb the repair and remodeling structural cells and lung tissues, resulting in COPD. [35][36][37][38] In concordance with related reports, [39][40][41] we found that COPD was linked to cigarette smoking intensity with a significant dose-response relationship. The finding was consistent with the related study of Forey et al (2011) reporting that the amount smoked and packs-years was attributable to increased risk of COPD, and affirming the causal relationship between COPD and cigarette smoking.…”
Section: Discussionsupporting
confidence: 91%
“…[33][34][35] Other evidence has illustrated via the possible roles regarding aging hallmarks including genomic instability, deregulated nutrient sensing, cellular senescence and stem cell exhaustion that disturb the repair and remodeling structural cells and lung tissues, resulting in COPD. [35][36][37][38] In concordance with related reports, [39][40][41] we found that COPD was linked to cigarette smoking intensity with a significant dose-response relationship. The finding was consistent with the related study of Forey et al (2011) reporting that the amount smoked and packs-years was attributable to increased risk of COPD, and affirming the causal relationship between COPD and cigarette smoking.…”
Section: Discussionsupporting
confidence: 91%
“…Although the nature and extent of these benefits remain unclear, we previously reported that in vivo AM carbon particulate loading is inversely related to capacity to produce an effective antibacterial response ( Rylance et al, 2015 ) and thus speculate that reduced AMBC loading from use of a cleaner cookstove reduces the risk of lower respiratory tract infection. In addition, since chronic exposure to biomass smoke is associated with lung function changes that are compatible with chronic obstructive airways disease, significant reductions in inhaled PM dose from cleaner cookstoves may attenuate the accelerated lung function decline thought to occur in this population of women ( Montes de Oca et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ex-smokers and current-smokers were defined as those who smoked ≥100 cigarettes in their lifetime, the former having quitted smoking for at least a year at the time of interview [11]. Biomass exposure was defined as exposure to biomass smoke from the burning of wood or charcoal for ≥100 h per year [12]. PB-FEV 1 was expressed in percent of predicted value based on the patients' age, gender, height, and ethnicity (PB-FEV 1 % predicted) [13].…”
Section: Methodsmentioning
confidence: 99%